Anoxic ATP depletion in neonatal mice brainstem is prevented by creatine supplementation. Issue 3 (1st May 2000) - Wilken, B; Ramirez, J M; Probst, I; Richter, D W; Hanefeld, F
Abstract : BACKGROUND: Sufficient ATP concentrations maintain physiological processes and protect tissue from hypoxic damage. With decreasing oxygen concentration, ATP synthesis relies increasingly on the presence of phosphocreatine. AIM: The effect of exogenously applied creatine on phosphocreatine and ATP concentrations was studied under control and anoxic conditions. METHODS: Pregnant mice were fed orally with creatine monohydrate (2 g/kg body weight/day). Brainstem slices from these mice pups were compared with those from pups of non-creatine supplemented pregnant mice. Measurements were performed under normoxic and anoxic conditions. In addition, brainstem slices from non-creatine treated mice pups were incubated for 3 hours in control artificial cerebrospinal fluid (CSF) (n = 10) or in artificial CSF containing 200 μM creatine (n = 10). ATP and phosphocreatine contents were determined enzymatically in single brainstem slices. RESULTS: ATP concentrations were in the same range in all preparations. However, there was a significant increase of phosphocreatine in the brainstems from pups of creatine fed mice when compared with the brainstems of pups from non-creatine treated mice or in non-incubated brainstems of control animals. After 30 minutes anoxia, ATP as well as phosphocreatine concentrations remained significantly higher in creatine pretreated slices compared with controls. CONCLUSION: The data indicate that exogenous application of creatine is effective in neuroprotection.